Validation of Finite Element Models for the Earthquake Simulator of Steel Storage Racks Using Full-Scale Shaking Table Tests - Yilmaz, Fuat; Alemdar, Fatih (LATIN AMER J SOLIDS STRUCTURES, 2026)
This study investigates the down-aisle seismic performance of a full-scale 3D cold-formed steel rack system using shaking table tests. The rack system was tested using scaled Northridge earthquake records, and the dynamic responses were evaluated during the test. The results demonstrated that the rack response remained essentially elastic up to approximately 50% of the Northridge intensity, beyond which pronounced inelastic behavior, approximately 50% stiffness degradation, and permanent drifts were observed. The experimental results were validated using an FE analysis, with substantial agreement in the elastic-to-mildly inelastic range, with similarity ratios of approximately 80%. However, differences were observed in the response values at the higher excitation intensities due to the high pallet sliding and connection slip during the test, which could not be accurately reflected in the FE model. It was observed that pallet sliding and connection friction, rather than member strength alone, governed the response under strong shaking and should be explicitly considered in advanced numerical models and in the seismic assessment of steel racks.
Keywords: Shaking table test; Finite element analysis; Storage rack systems; Down-aisle direction; Seismic analysis.; SEISMIC BEHAVIOR; CONNECTION; Engineering; Mechanics